The role of tacit knowledge on service quality – An applied Study on the Faisal Islamic Bank of Sudan – - Gadeen, Inaam Moustafa (Journal of Economic, Administrative and Legal Sciences, 2021)
Knowledge has already been highlighted as the most crucial component for the organization and competitiveness of banking institutions. However, the role of tacit knowledge on service quality remains unclear. The purpose of this study was to understand the role of tacit knowledge dimensions including qualification, training, experience, and intuition on the quality services of Faisal Islamic Bank of Sudan. The study population consisted of various levels of employees and administrative staff. The information was collected through a questionnaire as a study tool depending on purposive sampling and descriptive-analytical method. The results showed that the bank is using knowledge dimensions to improve banking service, however, there was no variation on knowledge application among the respondents, although, the combination of tacit knowledge dimensions showed a significant impact on the quality of banking service. This finding suggests the adoption of tacit knowledge to improve the quality of service at the bank. Further, the temporary engagement of foreign experts would be a better choice for the capacity building of local staff and improvement of banking services. Further study to investigate the role of tacit knowledge on innovation management of banking services in Sudanese banks is recommended.
Keywords: tacit knowledge; service quality; Faisal Islamic Bank of Sudan